SÍFILIS CONGÊNITA EM CAMPO GRANDE, MATO GROSSO DO SUL: CARACTERIZAÇÃO CLÍNICO-EPIDEMIOLÓGICA E DESCRIÇÃO DA CONDUTA HOSPITALAR PÓS-NASCIMENTO DOS CASOS CONFIRMADOS - CÁSSIA DE PAULA PIRES (2021)
Introduction: Syphilis is a sexually transmitted infectious disease registered for the first time almost 500 years ago with an increasing incidence in recent years. Syphilis is mostly transmitted through unprotected sex, but it can also be transmitted vertically, that is, from the placenta to the foetus during pregnancy, when the infected pregnant woman does not carry out the treatment or treat it improperly (BRASIL, 2020a). Prenatal care when performed improperly is one of the biggest factors for the high incidence rate of congenital syphilis (SONDA et al, 2013). Despite much talk about congenital syphilis, few studies address the immediate postpartum follow-up and up to the child's 18 months of life, this period being extremely important for the control of the disease and its complications. Objective: Describe clinical and epidemiological characteristics of pregnant women and newborns exposed to T. pallidum and hospital care for these newborns in the municipality of Campo Grande, Mato Grosso do Sul, from 2013 to 2018 Material and methodology: This is a descriptive cross-sectional study, based on secondary data from notifications of gestational and congenital syphilis reported to SINAN and on the review of medical records of cases of congenital syphilis from 4 hospitals in Campo Grande/MS. Associations between the presence of signs and symptoms suggestive of congenital syphilis (outcome) and clinical-obstetric and epidemiological characteristics of pregnant women (explanatory variables or covariates) were evaluated using the chi-square test or Fisher's exact test, when applicable. The odds ratio was also used as a measure of association and the relationship between the outcome and the explanatory variables was assessed using a logistic regression model. Results: Between 2013 and 2018, 2458 cases of gestational syphilis and 672 children with congenital syphilis were reported in SINAN. Regarding gestational syphilis, the year 2018 had the highest incidence, with 44.4 cases per 1000 live births, mostly young women, brown and with low education. In relation to congenital syphilis, 2017 had the highest incidence, with 10.8 cases per 1000 live births. The covariates alcoholism, prenatal care, number of prenatal visits, maternal treatment regimen and time of maternal diagnosis were associated with the outcome with a p-value less than or equal to 0.20 and were included in the regression model. Of these, only the number of prenatal visits remained in the final model as an explanatory variable, which suggests the possible protective effect of this variable on the occurrence of signs and symptoms related to congenital syphilis. Hospital conduct was considered inadequate in 62.3% of cases, especially due to non-performed neonatal screening tests, such as long bone x-ray, lumbar puncture and blood count, in addition to a treatment protocol with Penilicin that was inadequate for the clinic presented. Conclusion: Such findings are extremely important to know the profile and reasons for discontinuing treatment, in order to establish strategies that encourage the formation of links between the levels of health care and family / health team. Since the majority of newborns were not properly managed, greater force is recommended for the treatment and conduct criteria recommended by health authorities.